Respuesta :

If the one factor of the function is (x - 4). Then the other two factor of the function will be (2x + 1) and (x + 1).

What is a factorization?

It is a method for dividing a polynomial into pieces that will be multiplied together. At this moment, the polynomial's value will be zero.

(x - 4) is the factor of the function.

f(x) = 2x³ - 5x² - 11x - 4

Then the factor of the function will be

f(x) = 2x³ - 5x² - 11x - 4

f(x) = 2x³ + x² - 6x² - 3x - 8x - 4

f(x) = x²(2x + 1) - 3x (2x + 1) - 4(2x + 1)

f(x) = (2x + 1)(x² - 3x - 4)

f(x) = (2x + 1)(x² - 4x + x - 4)

f(x) = (2x + 1)[x(x - 4) + 1 (x - 4)]

f(x) = (2x + 1)(x + 1)(x - 4)

More about the factorization link is given below.

https://brainly.com/question/6810544

#SPJ1